Home automation under EMA's intelligent energy system initiatives - Cheah, Peng Huat. (2013)
With the launching of Intelligent Energy System (IES) pilot project in Singapore, 4,500 smart meters will be installed in various residential, commercial and industrial locations, including the Nanyang Technological University (NTU) campus, the CleanTech Park at Jalan Bahar and the Punggol Eco-Precinct. The purpose of the IES pilot project is to test and evaluate new applications and intelligent technologies around a smart grid to enhance its efficiency and robust resilience. It will serve as a test bed for Singapore power grid to become smarter and cleaner in the future.